8 major ways to use today's technology to lower energy usage : (and they're not solar, wind, and nuclear) - Ayres, Robert U. (FTPress Delivers elements., 2010)
This Element is an excerpt from Crossing the Energy Divide (ISBN: 9780137015443) by Robert U. Ayres and Edward H. Ayres. Available in print and digital formats. Finally: a coherent, integrated energy strategy based on techniques and technologies that have already been proven in the real world! We envision a national energy strategy with eight main components. One (increased energy efficiency of consumer products, including automobiles) has received serious media attention. Two others (increased energy efficiency in buildings and industrial plants, and decentralized electric power) have received moderate attention in industry and academia, but little public discussion. Few know the other five. Yet all eight have proven productive....